2009
DOI: 10.1007/s10498-009-9061-8
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Element Patterns in the Karst Terrains of Guizhou Province, China: Implication for Water/Particle Interaction

Abstract: The authors determine the concentrations of dissolved (\0.22 lm) rare earth elements (REE) and suspended particulate matter (SPM) of typical karst rivers in Guizhou Province, China during the high-flow period. The concentrations of acid-soluble REE extracted from SPM using diluted hydrochloric acid are also obtained to investigate water/ particle interaction in the river water. The dissolved REE contents in the river water are extremely low in the rivers of the study. The dissolved REE distribution patterns no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 51 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…Regarding REE migration, some studies have shown that REE are immobile during surface processes (Szczepanski and Ilnicki, 2014). However, some researchers have found that the mobility of REE was controlled by pH values (Han et al, 2009;Pazand and Javanshir, 2014) and REE was generally believed to be mobile at a lower pH value (Han and Liu, 2007;Migaszewski et al, 2014). However, there is In karst regions of the Southwest (SW) China, the degradation of ecosystems has led to many ecological problems, such as Karst Rocky Desertification.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding REE migration, some studies have shown that REE are immobile during surface processes (Szczepanski and Ilnicki, 2014). However, some researchers have found that the mobility of REE was controlled by pH values (Han et al, 2009;Pazand and Javanshir, 2014) and REE was generally believed to be mobile at a lower pH value (Han and Liu, 2007;Migaszewski et al, 2014). However, there is In karst regions of the Southwest (SW) China, the degradation of ecosystems has led to many ecological problems, such as Karst Rocky Desertification.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their special electron configuration in the outer shell, Ce and Eu occur as Ce 4+ and Eu 2+ ; the Eu anomaly, that is its deviation from the neighboring elements, is the petrogenesis of rocks in the drainage basin, and that of Ce is due to Ce (III) being oxidized to Ce (IV) during weathering. The two anomalies (Ce and Eu) are defined as follows: Ceanomaly=2true(normalCnormale/normalCnormale*true)/true(normalLnormala/normalLnormala*+normalPnormalr/normalPnormalr*true) Euanomaly=2true(normalEnormalu/normalEnormalu*true)/true(normalSnormalm/normalSnormalm*+normalGnormald/normalGnormald*true) where Ce*, La*, Pr*, Eu*, Sm*, and Gd* represent the concentrations of the respective REE in the PAAS. The Ce anomaly and the Eu anomaly represent the deviation of Ce and Eu concentrations from those expected from a linear interpolation of the concentrations of La and Pr and of Sm and Gd, respectively, in the PAAS‐normalized REE patterns of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their special electron configuration in the outer shell, Ce and Eu occur as Ce 4þ and Eu 2þ ; the Eu anomaly, that is its deviation from the neighboring elements, is the petrogenesis of rocks in the drainage basin, and that of Ce is due to Ce (III) being oxidized to Ce (IV) during weathering. The two anomalies (Ce and Eu) [31][32][33] are defined as follows:…”
Section: Data Treatmentmentioning
confidence: 99%
“…Secondary forest land and shrub land: 45%; agricultural land: 50% Note: MAT, mean annual temperature; MAP, mean annual precipitation. Data were cited from [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%